To find \( f(-2) \) for the function \( f(x) = 3x^2 - 6x + 2 \), we will substitute \(-2\) for \(x\):
\[ f(-2) = 3(-2)^2 - 6(-2) + 2 \]
Calculating each term step-by-step:
- \( (-2)^2 = 4 \)
- \( 3(-2)^2 = 3 \cdot 4 = 12 \)
- \( -6(-2) = 12 \)
- Now substituting everything in:
\[ f(-2) = 12 + 12 + 2 \]
- Combine the values:
\[ f(-2) = 12 + 12 + 2 = 26 \]
Thus, \( f(-2) = 26 \).
Since none of the provided options match 26, it's possible that there was an error in the options. Double-check that you've provided the correct function or choices. If none were incorrect, the computed \( f(-2) = 26 \) is accurate based on the given function \( f(x) \).